METHODOLOGY FOR DIMENSIONING OF A CENTER PIVOT IRRIGATION SYSTEM OPERATING WITH DRIPPER TYPE EMITTER - Almeida,Alex N. de (2017)
ABSTRACT: In Brazil, the conventional center pivot is widely used for irrigation of agricultural crops and its use has grown continuously. However, when improperly managed, it facilitates the development of diseases in all parts of the plant, with a direct effect on productivity, besides favoring losses of water by evaporation. The drip may be an alternative, since it minimizes the losses and does not wet the aerial parts of the plants, thereby reducing the incidence of diseases. A new system called localized mobile drip irrigation (IRGMO) is being developed in an attempt to combine the practicality and rusticity of the center pivot with the efficiency and water savings of the dripping irrigation systems. This fusion system is the central pivot with drip irrigation system for water distribution in the soil surface. This study aims to present a calculation methodology for the design of IRGMO system and compare it with conventional systems. It is concluded that this methodology allows the design of the IRGMO and that this new technology allows a savings of approximately 99% in a number of drip tubes compared to the conventional system with fixed drip irrigation lines in the field.